Base-cleavable microarrays for the characterization of DNA and RNA oligonucleotides synthesized in situ by photolithography - Lietard, Jory (Royal Society of Chemistry, 2014)

(untitled)
Assessing synthesis efficiency, errors, failed deprotections, and chemical and enzymatic degradation of oligonucleotides on microarrays is essential for improving existing in situ synthesis methods, and for the development of new chemistries. We describe the use of LC-MS to analyse DNA and RNA oligonucleotides deprotected and cleaved under basic conditions from microarrays fabricated using light-directed in situ chemistry. The data yield essential information on array quality and sequence identity.